Youth perceptions toward corruption and integrity: Indonesian context - O. Sihombing, Sabrina (Kasetsart Journal of Social Sciences, 2018)
Corruption is a crime against humanity-it destroys the country and infects every level of government. Country development is inhibited and poverty increases. Youth, which is the hope of the nation, plays an important role in the fight against corruption. Attitudes towards the fight against corruption and the importance of understanding integrity need to be instilled from a young age. However, not many researchers have investigated or tried to understand the perceptions of young people against corruption and integrity, especially in the Indonesian context. Thus, this research identified youth perceptions toward corruption and integrity. This paper describes the first stage (item generation) in developing a scale for corruption and integrity. Data were collected among Indonesian youth through an open-ended questionnaire and in-depth interviews. The results showed that Indonesian youth are not really familiar with the word integrity. More than half of the respondents could not define the word. From those who could, honesty was perceived as a main characteristic of integrity. Indonesian youth defined corruption as taking away the rights of others. They pointed out that taking away others money is an example of corruption. All the research findings combined with the literature review on corruption and integrity will become indicators to measure corruption and integrity in the next steps of the scale development.